Sintesis Lapis Empat Fasa Aurivillius Ca1-xBaxBi3,5La0,5Ti4O15 Dengan Metode Lelehan Garam - Zulhadjri; Silpa , Riga Oktry; Rahmayeni; Pratiwi, Nurul (Departemen Kimia Universitas Andalas, 2024)
The four-layer Aurivillius phase Ca1-xBaxBi3.5La0.5Ti4O15 (x = 0.2, 0.4, 0.6, 0.8, and 1) has been synthesized by molten salt method. The effect of varying x on the structure, morphology, and dielectric properties was studied. X-ray diffraction (XRD) and Le Bail refinement revealed that the compounds with the composition x = 0, 0.2, and 0.4 were single-phase product with orthorhombic A21am structure, whereas for higher x value (composition of Ba doped), a Ba2TiO4 impurity is found in products. Changes in unit cell volume were investigated, and the size increased with larger x. The substitution of larger Ba2+ ions resulted in a shorter Ti-O bond, shifting vibration mode to higher wave number that showed in FTIR spectra. SEM images show anisotropic plate-like grain with distributed particle sizes at 1.9 – 3.1μm. The dielectric constant values decrease with increasing x, otherwise the dielectric loss values increase for x = 0 and 0.2, however decrease for x = 0.4. The resulting Aurivillius compound has potential for applications in ferroelectric and piezoelectric devices.